Pengaruh Adopsi Teknologi, Budaya Organisasi, Kepemimpinan Transformatif terhadap Kinerja Karyawan - Irsyadi, Abdur Rahman; Rony, Zahara Tussoleha (Jurnal Ekonomi Manajemen Sistem Informasi, 2024)
Technology is one of the most crucial aspects in the development of an organization to ensure its survival and gain a competitive advantage. Organizations adopt technology to enhance operational efficiency and productivity, thereby improving employee performance. This research employs a literature review method, where the researcher explores literature from international journals and documents related to the adoption of technology and employee performance. The results indicate that technology adoption influences employee performance by enhancing operational efficiency, minimizing human error, and reducing routine tasks, enabling employees to complete their work more quickly. Additionally, technology adoption facilitates accelerated communication within the organization, thereby enhancing the performance of individuals and teams through effective collaboration. Technology adoption also affects determinants of employee performance, such as employee satisfaction and engagement, work-life balance, employee motivation, absenteeism rates, and burnout. However, the adoption of new technology often faces skepticism or even rejection from employees if organizations do not follow proper implementation steps. Therefore, organizations need to understand employees' emotions during the adoption of new technology and manage these negative effects by providing appropriate training, access to necessary devices, and empathy and open communication from the organization. Finally, an adaptive and agile organizational culture is highlighted as the most influential strategy for the success of organizational adoption.